Did backcrossing contribute to the origin of hybrid edible bananas? - De Langhe, Edmond (Oxford University Press, 2010)
BACKGROUND: Bananas and plantains (Musa spp.) provide a staple food for many millions of people living in the humid tropics. The cultivated varieties (cultivars) are seedless parthenocarpic clones of which the origin remains unclear. Many are believed to be diploid and polyploid hybrids involving the A genome diploid M. acuminata and the B genome M. balbisiana, with the hybrid genomes consisting of a simple combination of the parental ones. Thus the genomic constitution of the diploids has been classified as AB, and that of the triploids as AAB or ABB. However, the morphology of many accessions is biased towards either the A or B phenotype and does not conform to predictions based on these genomic formulae. SCOPE: On the basis of published cytotypes (mitochondrial and chloroplast genomes), we speculate here that the hybrid banana genomes are unbalanced with respect to the parental ones, and/or that inter-genome translocation chromosomes are relatively common. We hypothesize that the evolution under domestication of cultivated banana hybrids is more likely to have passed through an intermediate hybrid, which was then involved in a variety of backcrossing events. We present experimental data supporting our hypothesis and we propose a set of experimental approaches to test it, thereby indicating other possibilities for explaining some of the unbalanced genome expressions. Progress in this area would not only throw more light on the origin of one of the most important crops, but provide data of general relevance for the evolution under domestication of many other important clonal crops. At the same time, a complex origin of the cultivated banana hybrids would imply a reconsideration of current breeding strategies.